"Do mad people get endo or does endo make you mad?": Clinicians' discursive constructions of Medicine and women with endometriosis. (August 2019) - Young, Kate; Fisher, Jane; Kirkman, Maggie
Endometriosis, a common disease characterised as a "gynaecological disorder" in the medical literature, has attracted the attention of feminist scholars as a metaphorical meeting point for gender, knowledge and power. Based on interviews conducted with general practitioners and gynaecologists, we examined the language clinicians use to construct Medicine and women with endometriosis. We sought to identify whether these constructions endorsed or challenged historical discourses, and any implications for women with endometriosis. Clinicians endorsed Medicine as the authoritative knowledge on women and their bodies, and constructed Medicine as being about providing answers on, and doing things to, the body. Women with endometriosis were constructed as reproductive bodies with hysterical tendencies. The historical hysteria discourse was most often endorsed when discussing "difficult" women, referring to those for whom treatment was not helpful or who held a perception of their disease alternative to their clinician. The findings of our study are consistent with previous social analyses of medical literature on endometriosis and with women's reported experiences, suggesting these discourses to be prevalent in contemporary healthcare for endometriosis. Medical education needs to address the historical androcentric bias of medical knowledge and equip clinicians with the skills to address women's diverse needs.